High Availability Performance on OpenDayLight SDN Controller Platform (OSCP) Clustering and OpenDayLight with Heartbeat-Distributed Replicated Block Device (DRBD) - Andre Rizki Dewo Nugraha; Ridha Muldina Negara; Danu Dwi Sanjoyo (JURNAL INFOTEL, 2018)
Nowadays people are asking for a reliable network when technology at its limit. Software-Defined Network (SDN) is an answer to that problem of network development where all the control over the network becomes centralized. However, all services controlled by a centralized controller have a big disadvantage if the controller down. The High Availability (HA) is the solution. HA controller is divided into master and slave, when the master controller is down then the slave controller will respond to replace the function of the master controller. In this research, the system will be made by using two methods namely OpenDayLight SDN Controller Platform (OSCP) clustering and Heartbeat-DRBD (Distributed Replicated Block Device). OSCP clustering is a feature on the OpenDayLight controller that is ready to be used and only need to be configured, with OSCP the main and backup controller clustering will be on the connected cluster. Heartbeat-DRBD is an application commonly used to create High Availability systems on a server, but in this study will be used for the controller, Heartbeat will monitoring the main controller and if indicated to be down will move the resources to the backup controller with the DRBD application. From the simulation result shows that OSCP Clustering Failover and Failback average Time is 17 seconds while Heartbeat-DRBD is 23-45 seconds depends on how many switch and host are. While QoS parameters on both methods have similar value. It can be concluded that the High Availability system with OSCP Clustering method is more stable and good rather than Heartbeat-DRBD method to apply in a network.